Christians in Caesar's household : the emperors' slaves in the makings of Christianity - Flexsenhar, Michael, III, 1984- (Inventing Christianity., 2019)
"Examines the role of the Roman emperors' slaves in the rise of Christianity, and how imperial slaves were essential to early Christians' self-conception as a distinct people in the Mediterranean"--Provided by publisher